Fabrication of High Frequency Electromagnetic Waves Absorber Sheets by Use of Iron Oxide Nanostructures - mostafa arjomandi lari; saeed parhoodeh; ali rohani sarvestani; ghader alahverdi (Fasa University of Medical Sciences, 2019)
Background & Objective: The necessity of using wireless communications and the use of electromagnetic waves in today's world is obvious to everyone. Using of these equipment and development of them, although have many benefits but causes some anxiety on the way in which they influence on environment. One of the most effective ways of decreasing the unwanted effects of these waves is using of the absorber coatings of these waves. Materials & Methods: First, iron chloride powder was added to the aqueous solution of poly vinyl alcohol. Then, aqueous solution of sodium hydroxide was added to it. Subsequently, the iron oxide nanostructures that appeared in the bottom of the dish as sediment were collected by using filter paper and then washed several times with deionised water and ethanol. From the synthesized materials, sheets of thickness of 0.5 and 1 mm were made. Results: X-ray diffraction results proved the synthesis of iron oxide (Fe3O4). The analysis also showed that the synthesized nanostructures have a cubic structure and the average size of crystallites is 12 nm. The electron microscopy images showed that the nanostructures have a sheet-like shapes and their thickness are about 30 nm. The results of the absorption of electromagnetic waves in the range of 8 to 18 GHz showed that iron oxide nanostructures can absorb microwave waves in this range, which absorption increases in greater thicknesses. Conclusion: Coatings containing iron oxide nanostructures can act as microwave absorber and they could have an effective role in eliminating or reducing the unwanted effects of electromagnetic waves.